Sustainable river: the role of non-structural measures and public outreach programmes - Husin, Nor Azilah; Mariyanti, Eka; Saad, Mazni; Noor, Ahmad Fuad (2021)
The pollution level in the Klang River is high. The state government is working to address this issue. The study aims to determine the sustainability of the river through non-structural interventions and public outreach initiatives. Lembaga Urus Air Selangor (LUAS), Department of Irrigation and Drainage (DID), Klang Local Council (MPK), and Shah Alam Local Council (MBSA) provided a total of 82 accessible data. The river community and completed an adapted questionnaire. The persons in charge of river cleaning in related sectors. For the study, SPSS Version 22.00 is used to analyse data. The finding showed that Cross-sectoral Collaboration (CSC) and Public Outreach Programme (POP) significantly roles on Sustainable River Cleaning.